MENGOPTIMALKAN WORK LIFE BALANCE DAN PERFORMANCE APPRAISAL UNTUK MENINGKATKAN MOTIVASI KERJA DI BANK XYZ BOGOR - Ramadhani, Novelyne Darisa Putri; Sary, Fetty Poerwita (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
This research was conducted on employees of Bank XYZ Bogor. The purpose of conducting this research is to find out how work life balance, performance appraisal and work motivation of employees of Bank XYZ Bogor, find out how work life balance affects work motivation, performance appraisal affects work motivation, and to find out how work life balance influences and performance appraisal on the work motivation of Bank XYZ Bogor employees. In this study, the authors used quantitative research methods with causality descriptive research types. Sampling used a non-probability sampling method and the type of sample used was a saturated sampling technique. The samples in this study were employees of Bank XYZ Bogor, totaling 113 respondents. The data analysis technique used is descriptive analysis and multiple linear regression. The results of the descriptive analysis show that the level of work life balance and performance appraisal is in the good category while the level of work motivation is in the high category. based on the results of multiple linear regression analysis shows that there is a positive and significant influence between work life balance and performance appraisal on employee motivation. The results of the analysis of the coefficient of determination test obtained an R-square value of 0.692, which means that 69.2% of Bank XYZ Bogor employees' work motivation is influenced by work life balance and performance appraisal. Then the remaining 30.8% is influenced by other variables not examined in the following research.